Slap and tap teaching strategy: an intervention in overcoming student reticence - Dayawon, Marinel P. (Opción, 2019)
This study aimed to explore the effectiveness of the slap and tap method that will change the mindset of shy students in communicating their ideas in the classroom. Qualitative design is used with triangulation through participant observation, focus group discussion and interview. As a result, reticent students when involved in game activities through a slap and tap strategy, writing their clustered ideas, using sticky notes is excited, confident in sharing ideas. In conclusion, the strategy made a significant transformation of the shy students and it also sustained the interest of potential students as reflected in their journal logs and testimonies.